A hybrid photoelectrode with plasmonic Au@TiO2 nanoparticles for enhanced photoelectrochemical water splitting1. Issue 40 (28th October 2015) - Peerakiatkhajohn, Piangjai; Butburee, Teera; Yun, Jung-Ho; Chen, Hongjun; Richards, Ryan M.; Wang, Lianzhou
<x xml:space="preserve">Abstract</x> Herein we present a new p–n heterojunction photoelectrode design utilizing Cu2O and TiO2-P25 loaded with only 1 wt% Au@TiO2 plasmonic core–shell structure for the photoelectrochemical (PEC) process.